Parental Roles and Relationships in Immigrant Families An International Approach (Advances in Immigrant Family Research,, 2018)
This insightful volume presents important new findings about parenting and parent-child relationships in ethnic and racial minority immigrant families. Prominent scholars in diverse fields focus on families from a wide range of ethnicities settling in Canada, China, Israel, Italy, the Netherlands, and the United States. Each chapter discusses parenting and parent-child relationships in a broader cultural context, presenting within-group and cross-cultural data that provide readers with a rich understanding of parental values, beliefs, and practices that influence children's developmental outcomes in a new country. For example, topics of investigation include cultural variation in the role of fathers, parenting of young children across cultures, the socialization of academic and emotional development, as well as the interrelationships among stress, acculturation processes, and parent-child relationship dynamics. This timely reference: Explores immigration and families from a global, multidisciplinary perspective. Focuses on immigrant children and youth in the family context. Describes innovative methodologies for studying immigrant family relationships. Bridges the knowledge gap between immigrant and non-immigrant family studies. Establishes the relevance of these data to the wider family literature. Challenges long-held assumptions about immigrant families and parenting. Parental Roles and Relationships in Immigrant Families is not only useful to researchers and to family therapists and social workers attending to immigrant families, but also highly informative for persons interested in shaping immigration policy at the local, national, and global levels.